Improved non-Rake receiver based on two dimensional spread spectrum for WCDMA systems - TANG You-xi; SHAO Shi-hai; PAN Wen-sheng; LI Shao-qian (Tongxin xuebao)
A direct sequence spread spectrum receiver based on two dimensional spread spectrum for WCDMA systems was proposed. Unlike the conventional Rake receiver, the proposed receiver is motivated by idea of the transform domain design and makes full use of the multipath signals. And compared with the conventional Rake receiver, the proposed receiver is presented by computer simulations to support its bit error rate （BER） performance when it is difficult for the Rake receiver to distinguish each path accurately.